Aladdin & his magical lamp - Daynes,Katie (London: Usborne, 2007)
Young children can discover what happens when Aladdin finds a magic lamp in this mystical and magical story. This classic tale, with charming illustrations and simple text, will capture the imagination of children starting to read alone. 6 yrs+
Keywords: Children's stories